Inheritance of resistance to Fusarium wilt in pigeonpea - SINGH, I P; DHAR, VISHWA; CHAUDHARY, R G (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1995-96 on the inheritance of Fusarium wilt (Fusarium udum Butler) in pigeonpea [Cajanus cajan (L.) Millsp.]. Five resistant paents, viz ’Banda Palera’, ’DPPA 85-7’, ’DPPA 85-12’, ’PDA 85-1’ and ’ICPL 87119’ and 2 susceptible parents, viz ’Bahar’ and ’PDA 10’ were used. The parents, F1, F2, BC1 and BC2 generations were planted in the wilt-sick plot. Resistance to Fusarium wilt appeared to be dominant over susceptibility with monogenic inheritance.